2018
DOI: 10.22434/ifamr2017.0011
|View full text |Cite
|
Sign up to set email alerts
|

Towards high value markets: a case study of smallholder vegetable farmers in Indonesia

Abstract: The expansion of modern markets has significant implications for agriculture in many developing countries that provides both opportunities and challenges for smallholder farmers. The purpose of this paper is to analyse key determinants affecting farmers’ participation in high value markets, compared to traditional market. Face to face interviews based on a questionnaire were conducted with a sample of 126 smallholder vegetable farmers in the Manokwari region. Binary logistic regression and bivariate correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 26 publications
3
33
0
1
Order By: Relevance
“…Meanwhile, various species of medicinal plants from a city that are traded in the village market, usually are brought into the village market of Karangawangi, Cidaun, Cianjur by middlemen who bought various medicinal from the market centers, such as Ciwidey and Caringin Bandung city (Figure 7). Some studies on trading various species of edible plants, such as fruits, vegetables, cooking spices, and traditional medicines in the urban traditional markets in Indonesia have been carried out by scholars (Supangkat 2012;Susanti 2015;Yurlisa et al 2017;Maspaitella et al 2018). In addition, studies on medicinal plants traded in Indonesia and other countries have been undertaken by scholars (Idu et al 2010;Radriamiharrisoa et al 2015;Silalahi et al 2015;Irwanta et al 2015).…”
Section: Origin Of Medicinal Plant Species On the Village Marketmentioning
confidence: 99%
“…Meanwhile, various species of medicinal plants from a city that are traded in the village market, usually are brought into the village market of Karangawangi, Cidaun, Cianjur by middlemen who bought various medicinal from the market centers, such as Ciwidey and Caringin Bandung city (Figure 7). Some studies on trading various species of edible plants, such as fruits, vegetables, cooking spices, and traditional medicines in the urban traditional markets in Indonesia have been carried out by scholars (Supangkat 2012;Susanti 2015;Yurlisa et al 2017;Maspaitella et al 2018). In addition, studies on medicinal plants traded in Indonesia and other countries have been undertaken by scholars (Idu et al 2010;Radriamiharrisoa et al 2015;Silalahi et al 2015;Irwanta et al 2015).…”
Section: Origin Of Medicinal Plant Species On the Village Marketmentioning
confidence: 99%
“…The age of the household head could affect the household's participation in the market (see, for example, Maspaitella et al., 2018 ). It is observed in Kenya that smallholder farmers' participation in various markets, i.e., the sweet-potato market, is influenced by age ( Mutai et al., 2013 ).…”
Section: Output Price Support Buffer Stocks and Incomementioning
confidence: 99%
“…Educated farmers have a relatively high ability to obtain and process information about the projects, including NAFCO. Higher education will lead to an increased potential to acquire market information from various sources such as the media about the NAFCO program ( Maspaitella et al., 2018 ; Lapar et al., 2003 ). Educated farmers, therefore, are more likely to participate in the BSO due to their informed knowledge about NAFCO.…”
Section: Output Price Support Buffer Stocks and Incomementioning
confidence: 99%
“…Several studies, worldwide, have been conducted to analyze the enabling processes and conditions for family farmers' participation in the supermarket chains (BLANC et al, 2009;SAHARA et al, 2015;MASPAITELLA et al, 2017). However, the literature struggles to find consensus on positive conditioning factors required for family farmers' participation.…”
Section: Agribusinessmentioning
confidence: 99%
“…The literature widely addresses age as an enabling factor in family farmers' participation in the supermarket supply chains, though in conclusions they remain insignificant. Some studies stated that younger farmers are more willing to participate in the supermarket supply chains (SAHARA et al, 2015;MASPAITELLA et al, 2017), while others (RAO et al, 2012) concluded that older farmers are more suitable.…”
Section: Agementioning
confidence: 99%